Tubulocystic renal carcinoma: a clinical perspective - Hora, Milan; Urge, Tomáš; Eret, Viktor; Stránský, Petr; Klečka, Jiří; Kreuzberg, Boris; Ferda, Jiří; Hyršl, Luboš; Breza, Ján; Holečková, Petra; Mego, Michal; Michal, Michal; et al. (World journal of urology, 2011)
INTRODUCTION: Tubulocystic renal carcinoma (TCRC) is a recently described neoplastic entity. To date, clinicopathological features on less than hundred cases of these rare tumours have been characterized exclusively in the pathological literature. Herein, we present five additional cases emphasizing clinical aspects on these rare renal neoplasms. MATERIAL AND METHOD: Cases diagnosed as TCRC were retrieved and reviewed from the routine and consultation files of the Pilsen tumour registry comprising over 20,000 cases of renal tumours. RESULTS: All patients were men, mean age 56 years (range 29-70). Features on computed tomography (CT) were in two cases Bosniak III, one IV and two were solid tumours. In four patients, nephrectomy was performed, and one patient underwent resection. At the time of surgery, two patients had metastases. In one case, both primary tumour and metastases were active on FDG positron emission tomography (PET)/CT. Both patients with metastatic disease were treated with sunitinib with partial response. One patient died 26 months postoperatively and the other patient is alive 5 months after surgery. Three patients with localized tumours are without evidence of disease 31, 28 and 7 months after surgery. In one case, the resected tumour was histologically combined with a papillary renal cell carcinoma (PRCC). CONCLUSION: TCRC occurs predominantly in men with a wide age range. TCRC frequently displays a cystic component which may render a radiological classification of Bosniak III or IV. FDG PET/CT is helpful in the detection of metastases. TCRC has definitive malignant potential. Our findings support a possible relationship to PRCC. The tyrosine kinase inhibitor sunitinib may be used a therapeutical agent with partial response and temporary effect.
Keywords: výsledek terapie; kombinovaná terapie; Sunitinib; nádory ledvin; Pyrroles; Male; Combined Modality Therapy; protinádorové látky; karcinom z renálních buněk; indoly; Adult; Kidney Neoplasms; Aged; dospělí; mužské pohlaví; senioři; pyrroly; sunitinib; nefrektomie; Treatment Outcome; lidé; Humans; Indoles; Carcinoma, Renal Cell; Nephrectomy; lidé středního věku; Antineoplastic Agents; Middle Aged